2005
DOI: 10.1002/pbc.20598
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and home chemotherapy for children with leukemia: A randomized cross‐over study

Abstract: With few differences noted between groups, these results indicate preliminary support for administrating some or all of a child's chemotherapy at home. Home chemotherapy was associated with specific improvements and decrements in parent reported QOL. No effects were seen on burden of care, adverse events, or cost. Overall, young age adversely affected QOL, burden of care, and adverse events. These data provide important information to families and caregivers as they consider home or hospital-based therapy in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 26 publications
2
70
0
2
Order By: Relevance
“…In some studies, differences between the quality of life of hospitalized patients and those receiving ambulatory chemotherapy were reported (35,36). In this study, though not statistically significant, in patients receiving therapy while hospitalized lower quality of life scores were detected when compared with other groups.…”
Section: Discussionmentioning
confidence: 43%
“…In some studies, differences between the quality of life of hospitalized patients and those receiving ambulatory chemotherapy were reported (35,36). In this study, though not statistically significant, in patients receiving therapy while hospitalized lower quality of life scores were detected when compared with other groups.…”
Section: Discussionmentioning
confidence: 43%
“…In the Greater Toronto Area, pediatric patients with acute lymphoblastic leukemia were enrolled onto a randomized crossover study in which patients acted as their own controls, receiving chemotherapy at home for 6 months and subsequently in hospital for 6 months, and vice versa. The study included administration of two different chemotherapeutic agents (cytosine arabinoside and low-dose methotrexate) 5 . In that study, the IV chemotherapy was prepared by the community pharmacy, delivered to the patient's home, and administered by a trained community nurse 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown improved QOL parameters when patients are offered ambulatory and home chemotherapy [3,22,23]. Further studies may be needed to confirm this assumption among patients from underserved communities.…”
Section: Discussionmentioning
confidence: 99%